2014
DOI: 10.1117/12.2039349
|View full text |Cite
|
Sign up to set email alerts
|

Multiline possibility of Nd:YAlO3laser in spectral range 1.3-1.5 µm

Abstract: The goal of our research was investigation of diode pumped Nd:YAlO 3 (Nd:YAP) laser tuning possibility in spectral range of general interest 1.3 -1.5 μm. Laser radiation in this region is very required for many applications in medicine, atmospheric physics, and spectroscopy due to high absorption of this radiation in liquid water and water vapors. We use 1.0 at. % doped Nd:YAP active medium φ5 x 8 mm in dimensions. As a pumping source, a fibre-coupled 808 nm laserdiode was utilized. Two particular Nd:YAP laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In fact, to the best of our knowledge, there have been very few studies on simultaneous dual-and tri-wavelength Nd 3+ lasers operation around 1.4 μm. In 2014, Nemec et al [20] demonstrated two Nd: YAP-based dual-wavelength lasers at (1401.8, 1407.3 nm) and (1407.3, 1432.3 nm) by using a birefringent quartz plate. However, output powers in this publication were very limited and in fact there were no reports about the output powers.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, to the best of our knowledge, there have been very few studies on simultaneous dual-and tri-wavelength Nd 3+ lasers operation around 1.4 μm. In 2014, Nemec et al [20] demonstrated two Nd: YAP-based dual-wavelength lasers at (1401.8, 1407.3 nm) and (1407.3, 1432.3 nm) by using a birefringent quartz plate. However, output powers in this publication were very limited and in fact there were no reports about the output powers.…”
Section: Resultsmentioning
confidence: 99%